Comparison of Post-Operative Sensitivity in Composite Restoration Using Total Etch and Self Etch Dentine Adhesives - Afshan Jawaid, Anny Memon, Ashar Hussain, Muhammad Sidique Qazi, Muhammad Muslim Khahro, Talha Asad Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Post-operative sensitivity remains a common clinical concern in composite restorations, often influenced by the type of dentin adhesive used. Objective: To compare post-operative sensitivity in composite restorations using total-etch and self-etch dentin adhesive systems. Methodology: A randomized controlled trial was conducted in the Department of Operative Dentistry, Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro, over a six-month period. A total of 242 patients aged 15–60 years with Class I carious lesions were recruited and randomized into two groups: Group A (n = 121) received restorations using a total-etch adhesive system, and Group B (n = 121) received restorations with a self-etch adhesive system. Post-operative sensitivity was assessed at 1, 2, and 4 weeks using a Visual Analogue Scale (VAS) and clinical sensitivity tests (cold, hot, and bite). Data were analyzed using SPSS version 20, with chi-square applied for categorical comparisons. Results: Out of 242 patients, 232 (95.90%) completed follow-up. At final evaluation, overall 70.70% reported no sensitivity, while 29.31% experienced post-operative sensitivity. In the total-etch group, 42.90% of patients reported sensitivity compared to only 15.0% in the self-etch group, a statistically significant difference (p < 0.00001). Cold sensitivity was the most frequent trigger, particularly during the first week, and gradually decreased over time in both groups. No significant associations were found with gender, age, or tooth type. Conclusion: Self-etch adhesive systems demonstrated superior performance in reducing post-operative sensitivity compared to total-etch systems. Keywords: Post-operative sensitivity, composite restoration, total-etch adhesive, self-etch adhesive.